Percorsi recenti degli studi medievali Atti delle giornate di studio in occasione del ventennale del Dottorato di ricerca in Storia medievale (Firenze, 27-28 gennaio 2004) - Andrea Zorzi (Scuole di dottorato, 2008)
This book brings together the proceedings of the study days organised to mark the twentieth anniversary of the Florence University PhD course in Mediaeval History. It offers, first and foremost to the broad public of young scholars of Italian mediaeval history, an overview of conceptual approaches to the major issues characterising the various ambits of mediaeval research over the last twenty years.